Estudo comparativo entre as percepções da imagem organizacional nos dois segmentos de público interno de uma instituição de ensino superior privado de Santa Maria - Alvarenga, Aline da Silva (2006)
This work presents a study about the perception of the organizational image from the two segments of the internal public at a Private Higher Education Institution in Santa Maria RS. The model used at the research was the measurement of organizational images through a questionnaire based on the eight MORGAN s (1996) metaphors. By means of this model of image perception, we attempted to stick out the differences among the organizational image perception of undergraduate students, administrative staff and undergraduate professors of College A, the chosen object to the study. The 38 items of the research instrument correspond to two found factors: Factor 1 Dynamic organization with a strategic view and Factor 2 Petty political and exploitive organization. The propositions are evaluated by means of concordance to seven points of a Likert-type anchored scale. The questionnaire was applied to a sample of 216 undergraduate students from two different undergraduate course of College A and, 35 administrative personnel and professors of these courses. After the tabulation, the data was analyzed with the SPSS Software, where statistical tests like the T-Student, Chi-Square and ANOVA were performed and a Factorial Analysis was carried out. Through the two drawn out factors and the worked variables it is important to emphasize that there was some difference in the images perceived by the two segments of internal public from College A. The comparative study allow us to say that the organizational image perception of College A is closer to Factor 1 Dynamic organization with a strategic view either for the undergraduate students or to the administrative personnel and professors of the undergraduate courses.